慈光弥勒学校初中八年级学生使用量词 “家”“间”与“所”的能力考察 KEMAMPUAN PENGGUNAAN KATA BANTU BILANGAN “JIA”, “JIAN” DAN “SUO” PADA SISWA/I KELAS 8 SMP SEKOLAH MAITREYAWIRA T.A. 2020-2021 - Sinar Anwar (Journal of Language, Literature and Teaching, 2022)
The purpose of this study was to describe the ability of 8th grade Junior High School students of Maitreyawira T.A. 2020-2021 in using the Number Auxiliary Words “jia”, “jian” and “suo”. To achieve this goal, the researchers used a quantitative descriptive research design in which the population was 128 students, and the sample was taken using the Cluster Random Sampling technique, namely 71 students in 8th grade Junior High School students Maitreyawira T.A. 2020-2021 as the sample of this research. The instrument and data collection technique used is to give test questions to the sample. The validity of this study uses content validity, and the calculation of the test questions for each word is 8 questions using the KR-20 formula. The reliability value of the auxiliary verb instrument "jia" is high, namely 0.64, the reliability value of the auxiliary verb instrument "jian" is 0.73 and the reliability value of the auxiliary verb instrument "suo" is 0.65. The analysis of the results of the student's ability test in using the auxiliary number "jia" showed an average of 58.63 which was included in the incompetent category, while the results of the student's ability test using the auxiliary number "jian" showed an average of 67.96 included in the poor category. competent and finally the results of the student's ability test in using the auxiliary number "suo" showed an average of 48.8 which was included in the incompetent category.Key Word: Ability to Use, Numbers Auxiliary Words, “jia”, “jian” “suo”